73.1k views
2 votes
1/4p+3/4(p−8)=11+1/4(12p+4)

User Dimos
by
5.8k points

1 Answer

2 votes

Answer:


\boxed{\bold{p=-9}}

Explanation:


\bold{ \cfrac{1}{4}\:p+\cfrac{3}{4}\left(p-8\right)=11+\cfrac{1}{4}\left(12p+4\right)}


\bold{\cfrac{1}{4}\left(12p+4\right)}

Multiply fractions:


\bold{\cfrac{1* \left(12p+4\right)}{4}}


\bold{\cfrac{12p+4}{4}}


\bold{\cfrac{1}{4}\:p+\cfrac{3}{4}\left(p-8\right)=11+\cfrac{12p+4}{4}}

Now, Multiply both sides by 4:


\bold {\cfrac{1}{4}\:p* \:4+\cfrac{3}{4}\left(p-8\right)* \:4=11* \:4+\cfrac{12p+4}{4}* \:4}


\bold {p+3\left(p-8\right)=12p+48}

Expand: Apply Distributive property:


\bold{p+3p-24=12p+48}

Combine like terms:


\bold{(p+3p):4p}


\bold{4p-24=12p+48}

Add 24 from both sides:


\bold{4p-24+24=12p+48+24}


\bold{4p=12p+72}

Subtract 12p from both sides:


\bold{4p-12p=12p+72-12p}


\bold{-8p=72}

Divide both sides by -8:


\bold{\cfrac{-8p}{-8}=\cfrac{72}{-8}}


\bold{p=-9}

______________________________________

User Vishwajit Palankar
by
6.2k points